The Colored Conventions movement Black organizing in the nineteenth century - Foreman, Pier Gabrielle; Casey, Jim 1985-; Patterson, Sarah Lynn (The University of North Carolina Press, 2021)
"This volume of essays is the first to focus on the Colored Conventions movement, the nineteenth century's longest campaign for Black civil rights. Well before the founding of the NAACP and other twentieth-century pillars of the civil rights movement, tens of thousands of Black leaders organized state and national conventions across North America. Over seven decades, they advocated for social justice and against slavery, protesting state-sanctioned and mob violence while demanding voting, legal, labor, and educational rights. Collectively, these essays highlight the vital role of the Colored Conventions in the lives of thousands of early organizers, including many of the most famous writers, ministers, politicians, and entrepreneurs in the long history of Black activism"--
Includes bibliographical references and index
Keywords: Geschichte 1800-1900; Bürgerrecht; Aktivismus; Politische Beteiligung; Selbstorganisation; Schwarze; USA; African Americans / Civil rights / Congresses / History / 19th century; Congresses and conventions / United States / History / 19th century; Congresses and conventions; United States; 1800-1899; History; Konferenzschrift -- 2015 -- Newark, Del.